DEVELOPMENT OF CREATIVE COMMUNICATIVE SKILLS OF FUTURE EDUCATORS - AS A PEDAGOGICAL PROBLEM - Avazbek Artiqboyevich Davronov (Web of Journals Publishing, 2023)
In this article, the importance of developing creative communicative skills of future pedagogues as a pedagogical problem, creative communicative skills, help to increase the ability of pedagogues to establish effective communication with students, exchange ideas, express their opinions, consult, create and find solutions given information about giving.
Keywords: Pedagogical, communicative, motivation, creativity, use of creativity, improvement of business acumen, probability and mastery.